1992
DOI: 10.1128/jb.174.23.7750-7756.1992
|View full text |Cite
|
Sign up to set email alerts
|

The gene coding for 3-deoxy-manno-octulosonic acid transferase and the rfaQ gene are transcribed from divergently arranged promoters in Escherichia coli

Abstract: The gene kd&4 in Escherichia coli codes for 3-deoxy-D-manno-octulosonic acid transferase, the enzyme responsible for attachment of the two 3-deoxy-D-manno-octulosonic acid residues that constitute the link between lipid A and the core oligosaccharide of the lipopolysaccharide. Cloning and subsequent sequencing of the region upstream of kdt4 revealed an open reading frame identified as the first gene (fiaQ) in an ia gene cluster. The kdt4 and raQ transcripts were identified, and the 5' ends of the transcripts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…It is predicted to have the potential of forming a stem-loop structure which (with some transcripts) may effectively sequester the lacZ ribosome binding site, leading to poor translation initiation (data not shown). Several other studies using this same and related vectors have reported low levels of enzyme activity (3,12,19,53). However, despite the low ␤-galactosidase reporter activity in these constructs, sequence modifications to the potential control elements led to changes in these activity levels that were consistent with changes in the actual transcript levels measured by primer extension.…”
Section: Resultssupporting
confidence: 57%
“…It is predicted to have the potential of forming a stem-loop structure which (with some transcripts) may effectively sequester the lacZ ribosome binding site, leading to poor translation initiation (data not shown). Several other studies using this same and related vectors have reported low levels of enzyme activity (3,12,19,53). However, despite the low ␤-galactosidase reporter activity in these constructs, sequence modifications to the potential control elements led to changes in these activity levels that were consistent with changes in the actual transcript levels measured by primer extension.…”
Section: Resultssupporting
confidence: 57%
“…Arakawa et al (1995) identified a weak homology between the JUMPstart sequence and a 54specific promoter sequence and suggested that it acts as a promoter. This is unlikely as the ops element is unable to direct transcription without an upstream promoter (Nieto et al, 1996) and, where transcript initiation sites of RfaHdependent operons have been mapped, the ops element lies in a non-translated leader sequence upstream of the first gene (Clementz, 1992;Leeds and Welch, 1996;Stevens et al, 1997).…”
Section: The Ops Element a Transcription Activation Sequence Conservmentioning
confidence: 99%
“…To determine the impact of GadE in such pathways, we analysed the DNA-binding properties of GadE to the promoter region of several gene targets whose products are involved in each pathway. The regulatory region of some of them has been described in detail previously: gadA (Castanie-Cornet De Biase et al, 1999), gadX (Tramonti et al, 2002), hdeAB (Arnqvist et al, 1994;Tucker et al, 2003), gltBD (Wiese et al, 1997), osmC (Bouvier et al, 1998), rcsA (Stout, 1996), rfaQGPSBIJYZK (Clementz, 1992) and ompC (Norioka et al, 1986). We characterized here the promoter region of hdeD.…”
Section: Dna-binding Properties Of Gadementioning
confidence: 99%